The coal deposits and coal mining of Svalbard (Spitsbergen and Bear Island) - Hoel, Adolf, 1879-; Norske videnskaps-akademi i Oslo. (Oslo : J. Dybwad, 1925)
Cover title. At head of title: Det Norske videnskaps-akademi i Oslo. Bibliography: p. 89-92. Mode of access: Internet.